Ag modified mesoporous bioactive glass nanoparticles for enhanced antibacterial activity in 3D infected skin model - Zheng, Kai; Balasubramanian, Preethi; Paterson, Thomas E.; Stein, René; MacNeil, Sheila; Fiorilli, Sonia; Vitale-Brovarone, Chiara; Shepherd, Joanna; Boccaccini, Aldo R. (Materials Science and Engineering C, 2019)
Bioactive glasses (BG)are versatile materials for various biomedical applications, including bone regeneration and wound healing, due to their bone bonding, antibacterial, osteogenic, and angiogenic properties. In this study, we aimed to enhance the antibacterial activity of SiO2-CaO mesoporous bioactive glass nanoparticles (MBGN)by incorporating silver (Ag)through a surface modification approach. The modified Ag-containing nanoparticles (Ag-MBGN)maintained spherical shape, mesoporous structure, high dispersity, and apatite-forming ability after the surface functionalization. The antibacterial activity of Ag-MBGN was assessed firstly using a planktonic bacteria model. Moreover, a 3D tissue-engineered infected skin model was used for the first time to evaluate the antibacterial activity of Ag-MBGN at the usage dose of 1 mg/mL. In the planktonic bacteria model, Ag-MBGN exhibited a significant antibacterial effect against both Pseudomonas aeruginosa and Staphylococcus aureus in comparison to non-engineered (Ag-free)MBGN and the blank control. Moreover, Ag-MBGN did not show cytotoxicity towards fibroblasts at the usage dose. However, in the 3D infected skin model, Ag-MBGN only demonstrated antibacterial activity against S. aureus whereas their antibacterial action against P. aeruginosa was inhibited. In conclusion, surface modification by Ag incorporation is a feasible approach to enhance the antibacterial activity of MBGN without significantly impacting their morphology, polydispersity, and apatite-forming ability. The prepared Ag-MBGN are attractive building blocks for the development of 3D antibacterial scaffolds for tissue engineering.
CRIS-Team Scopus Importer:2019-06-18
Keywords: 3D skin model; Antibacterial activity; Bioactive glasses; Nanoparticles; Silver

Angiogenic potential of boron-containing bioactive glasses: in vitro study - Balasubramanian, Preethi; Hupa, Leena; Jokic, Bojan; Detsch, Rainer; Grünewald, Alina; Boccaccini, Aldo R. (Journal of Materials Science, 2017)

Bilayered bioactive glass scaffolds incorporating fibrous morphology by flock technology - Balasubramanian, Preethi; Boccaccini, Aldo R. (Materials Letters, 2015)
We report for the first time on the combination of polymer replication method and flock technology to produce 45S5 bioactive glass (45S5 BG) scaffolds with a fibrous surface morphology suitable for tissue engineering (TE). In order to develop a fibrous morphology on the surface of the scaffolds, electroflocking was used with BG scaffolds serving as the substrate. Gelatin was used as the adhesive and short polyamide (PA) fibers were electroflocked on the top surface to produce scaffolds with anisotropic properties. In order to improve the stability of the adhesive (gelatin) and to create a better bonding between the fibers and the adhesive, a crosslinking step was carried out. The porosity on the surface could be tailored by varying the flocking time which, in turn, was shown to influence the packing density of the fibers. In vitro bioactivity study in simulated body fluid (SBF) was carried out and complete mineralization of the scaffold, including on the PA fibers, was detected and characterized using various techniques.
Keywords: Bioglass; Electroflocking; Osteochondral tissue engineering; Scaffold fabrication

Bi-layered porous constructs of PCL-coated 45S5 bioactive glass and electrospun collagen-PCL fibers - Balasubramanian, Preethi; Roether, Judith; Schubert, Dirk W.; Beier, Justus; Boccaccini, Aldo R. (Journal of Porous Materials, 2015)
A simple yet promising approach to construct bi-layered scaffolds using bioactive ceramics and biodegradable polymers is presented. This method involves two versatile fabrication techniques used in the field of TE: foam replication process and electrospinning. By the foam replication method, three-dimensional 45S5 bioactive glass (BG)-based scaffolds with high porosity, in the range of 95.8 ± 0.9 %, were produced. To improve the mechanical properties of the BG scaffolds, dip-coating using polycaprolactone (PCL) was performed, which led to a significant increase in the compressive strength of the scaffolds. In order to develop a bi-layered construct, bead-less submicrometric fibers of collagen-PCL were electrospun over the PCL-coated BG scaffolds. Surface morphology, surface properties and mechanical strength of the bi-layered construct were evaluated using scanning electron microscopy analysis, contact angle measurements and compressive strength testing, respectively. In vitro degradation of the collagen-PCL fibers in phosphate buffered saline and in vitro bioactivity of the bi-layered constructs in simulated body fluid were investigated. Formation of hydroxyapatite on the PCL-coated BG and along the morphology of the collagen-PCL fibers was ascertained using different characterization techniques. The bi-layered construct is intended for interface tissue engineering applications where the PCL-coated BG scaffold, which is highly bioactive, can serve as a support for the bone side and the composite collagen-PCL submicrometric fibers are intended for the cartilage side.
Keywords: Bioactivity; Electrospinning; In vitro degradation; Osteochondral region; Scaffold

Bioactivation of titanium dioxide scaffolds by ALP-functionalization - Sengottuvelan, Abirami; Balasubramanian, Preethi; Will, Julia; Boccaccini, Aldo R. (Bioactive Materials, 2017)

Bioactive glasses and glass-ceramics versus hydroxyapatite: Comparison of angiogenic potential and biological responsiveness - Bellucci, Devis; Braccini, Simona; Chiellini, Federica; Balasubramanian, Preethi; Boccaccini, Aldo R.; Cannillo, Valeria (Journal of Biomedical Materials Research Part A, 2019)
Different bioactive glasses (BGs), bioceramics, and their composites were extensively analyzed in terms of biological responsiveness and angiogenic potential. In particular several inorganic materials were considered, namely the widely used 45S5 BG, an experimental BG with low tendency to crystallize, other three experimental BGs doped with strontium and/or magnesium, a commercial hydroxyapatite (HA), and two BG–HA composites (with varying percentages of BG and HA). All these materials were ad hoc prepared and in vitro tested by means of an extensive biological analysis, such as MC3T3-E1 cell viability and proliferation by direct contact assay, alkaline phosphatase activity, mineralized matrix deposition analysis by alizarin red staining, as well as evaluation of angiogenic potential and vascular endothelial growth factor release using ST2 cells. Thus, this investigation allows gaining a deeper insight into the biological performance of different inorganic material categories, and to critically compare the different possible solutions, as bone/tissue substitutes for enhanced healing and repair, in terms of bioactivity and regenerative potential.
CRIS-Team Scopus Importer:2019-08-27
Keywords: angiogenesis; bioactive composites; bioactive glasses; bioceramics; in vitro biological tests; magnesium; strontium

Boron-containing bioactive glasses in bone and soft tissue engineering - Balasubramanian, Preethi; Büttner, Teresa; Miguez Pacheco, Valentina; Boccaccini, Aldo R. (Journal of the European Ceramic Society, 2018)
Keywords: Angiogenesis; Bioactive glasses; Bioactivity; Borate; Borosilicate; In vivo; Osteogenesis

Characterizing the degradation behavior of bioceramic scaffolds - Goudouri, Ourania Menti; Balasubramanian, Preethi; Boccaccini, Aldo R. (Elsevier Inc., 2016)
The use of bioceramic scaffolds for hard tissue repair, augmentation, and substitution is continuously increasing in many dental and medical applications. It is well established that the in vivo biodegradation and bioresorption of ceramic scaffolds at rates appropriate to tissue regeneration play a vital role in enabling new tissue formation. Furthermore, the various ionic by-products of biodegradation of scaffolding materials result in the enrichment of the microenvironment, which can affect, positively or negatively, the proliferation and activity of cells. Therefore, the factors affecting degradation or the extent of dissolution of the scaffolding materials are important. The aim of this chapter is to discuss the processes of biodegradation or bioresorption of bioceramic scaffolds in terms of the physical, chemical, and biocompatibility that occur when in contact with simulated body fluids, cells, or living tissue, focusing on the applied characterization techniques.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Bioactive Glasses; Bioceramics; In vitro/In vivo dissolution; Ion release; PH Changes; Weight Loss

Incorporation of Boron in Mesoporous Bioactive Glass Nanoparticles Reduces Inflammatory Response and Delays Osteogenic Differentiation - Zheng, Kai; Fan, Yuqian; Torre, Elisa; Balasubramanian, Preethi; Taccardi, Nicola; Cassinelli, Clara; Morra, Marco; Iviglia, Giorgio; Boccaccini, Aldo R. (Particle & Particle Systems Characterization, 2020)
Mesoporous bioactive glass nanoparticles (MBG) are multifunctional building blocks for tissue regeneration and nanomedicine applications. Incorporation of biologically active ions can endow MBG with additional functionalities toward promoted therapeutic effects. Here, boron is incorporated into MBG by using a sol–gel approach. The concentration of boron incorporated is controllable by tuning the amount of boron precursor. Two types of boron-doped MBG, namely 10B- and 15B-MBG (5.8 and 6.5 mol% of B2O3, respectively) are synthesized. Boron incorporation does not significantly influence the particle morphology. All synthesized particles exhibit a sphere-like shape with a size ranging from 100 to 300 nm. 10B- and 15B-MBG show large specific surface area (346 and 320 m² g−1, respectively) and pore volume. Both boron-doped MBG exhibit remarkable in vitro bioactivity and noncytotoxicity. Boron incorporation is shown to reduce the inflammatory response linked to macrophages as indicated by downregulated expression of pro-inflammatory genes. However, boron incorporation delays the osteogenic differentiation in osteoblasts as indicated by the downregulated expression of pro-osteogenic genes. The results demonstrate the promising potential of using boron-doped MBG to modulate inflammatory response for bone regeneration under inflammatory conditions, as shown in this study for the first time.
CRIS-Team Scopus Importer:2020-06-09
Keywords: bioactive glasses; bioactivity; boron; inflammatory response; osteogenic activity

Induction of VEGF secretion from bone marrow stromal cell line (ST-2) by the dissolution products of mesoporous silica glass particles containing CuO and SrO - Balasubramanian, Preethi; Salinas, Antonio J.; Sanchez-Salcedo, Sandra; Detsch, Rainer; Vallet-Regi, Maria; Boccaccini, Aldo R. (Journal of Non-Crystalline Solids, 2018)
Keywords: Angiogenesis; Bioactive glasses; Mesoporosity; Bone marrow stromal cells; Ion release

Influence of dissolution products of a novel Ca-enriched silicate bioactive glass-ceramic on VEGF release from bone marrow stromal cells - Balasubramanian, Preethi; Detsch, Rainer; Esteban-Tejeda, Leticia; Grünewald, Alina; Moya, Jose S.; Boccaccini, Aldo R. (Biomedical Glasses, 2017)

Ion Release, Hydroxyapatite Conversion, and Cytotoxicity of Boron-Containing Bioactive Glass Scaffolds - Balasubramanian, Preethi; Grünewald, Alina; Detsch, Rainer; Hupa, Leena; Jokic, Bojan; Tallia, Francesca; Solanki, Anu K.; Jones, Julian R.; Boccaccini, Aldo R. (International Journal of Applied Glass Science, 2016)
Keywords: bioactive glasses; bone tissue engineering; borate glasses; borosilicate glasses; scaffolds

Micro-computed-tomography-guided analysis of in vitro structural modifications in two types of 45S5 bioactive glass based scaffolds - Westhauser, Fabian; Ciraldo, Francesca; Balasubramanian, Preethi; Senger, Anne-Sophie; Schmidmaier, Gerhard; Moghaddam, Arash; Boccaccini, Aldo R. (Materials, 2017)
Keywords: Bioactive Glass; Maritime national sponge; Polyurethane foam; μCT; tissue engineering; in vitro; dissolution behavior

Oberflächenmodifikation von bioaktiven Glasstützstrukturen - Balasubramanian, Preethi (2016)
Bioactive glasses (BGs) continue to attract interest as promising materials for bone regeneration. In the broad family of BGs, boron containing systems, including B-doped silicate, borosilicate glasses and borate glasses, are being increasingly considered due to their attractive osteogenic and neovascularization properties. In this work, a new series of BGs based on the 13-93 composition (SiO2-CaO-Na2O-P2O5-K2O-MgO-B2O3) was prepared and three-dimensional scaffolds were produced by the polymer replica technique. The compressive strength of these scaffolds was found to be significantly higher than that of standard 45S5 Bioglass® scaffolds which is related to the higher densification rate of struts achieved by viscous flow during the sintering process. In vitro dissolution studies in cell culture medium were carried out over a period of 14 days and the formation of hydroxyapatite (HA) was confirmed using different characterization techniques such as Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR). The boron-based scaffolds immersed in cell culture medium exhibited a moderate release of B and Si ions which was measured using Inductively Coupled Plasma-Optical emission analyses. The effects of the ionic dissolution products (IDPs) of the boron-based BG scaffolds on mouse bone marrow stromal cells (ST2 cells) in vitro were ascertained, using an angiogenesis assay. The expression and secretion of angiogenic growth factor, vascular endothelial growth factor (VEGF) from ST2 cells were measured quantitatively using the VEGF ELISA Kit. Cellular response was found to be dependent on the boron content and the B release profile from the glasses corresponded to the positive/negative influence in their biological activity. Functionalizing the surfaces of these BG scaffolds with biologically active molecules or enzymes is a suitable strategy to enhance both the inorganic and biological responses of the biomaterial and to stimulate physiological tissue regeneration. Alkaline Phosphatase (ALP) is a metalloenzyme involved, significantly, in osteogenesis and is highly expressed in mineralized tissue cells. Silanization was performed, followed by ALP grafting on the surface of the BG scaffolds, which was confirmed by FTIR and enzymatic activity test, respectively. The ability of the boron-containing BG scaffolds, with and without ALP grafting, to stimulate VEGF from ST2 cells was determined. An in vitro osteogenic differentiation experiment, with and without the presence of osteogenic stimulating agents, was executed over a period of 14 days. It was determined that the ALP grafted to the surface of boron-containing scaffolds equated the performance of an osteogenic stimulating agent during the differentiation of ST2 cells. Cell viability and proliferation were determined using mitochondrial & LDH activity and BrdU (calorimetric) assay, respectively. Specific ALP activity and a mineralization assay revealed that the ALP-functionalized boron-containing scaffolds possess excellent capabilities to differentiate stromal cells into osteoblast-like phenotype. A preliminary subcutaneous implantation study in rats was carried out (by collaborators) to evaluate the performance of ALP-functionalized scaffolds in vivo. The influence of an enzyme (ALP) was established, in terms of ion release kinetics, directing better cell-matrix interactions, osteogenic differentiation and angiogenic potential, for bone regeneration applications. In summary, the combination of boron-containing BG scaffolds with the enzyme ALP has facilitated the inception of a promising strategy to enhance bone healing and regeneration.
Keywords: bioactive glasses; borate glass; tissue engineering; bone regeneration; borosilicate glass; angiogenesis

Preparation and in vitro characterization of silver-doped bioactive glass nanoparticles fabricated using a sol-gel process and modified Stöber method - El-Rashidy, Aiah A.; Waly, Gihan; Gad, Ahmed; Hashem, Azza A.; Balasubramanian, Preethi; Kaya, Seray; Boccaccini, Aldo R.; Sami, Inas (Journal of Non-Crystalline Solids, 2018)
The study aimed at preparing Ag-doped bioactive glass (BG) nanoparticles containing 5 wt% Ag2O using a new modified Stöber method (Ag-BGm) and the conventional sol-gel method (Ag-BGsg). The aim of employing the new Ag-doping mechanism is to implement a relatively short process to incorporate higher concentration of silver (Ag+) ions in an attempt to combine the antibacterial activity of silver with the bioactivity of BG. SEM and TEM micrographs showed that Ag-BGm nanoparticles were mondispersed, and spherical, while Ag-BGsg nanoparticles were formed of highly porous irregular agglomerated particles. A significantly higher silicon, calcium and silver ions release from the Ag-BGsg was evident, as compared to Ag-BGm, in deionized water (DIW). In vitro bioactivity test showed rapid bioactive properties of Ag-BGsg in simulated body fluid (SBF), as compared to Ag-BGm. Both BGs showed antibacterial effect against E. coli O157: H7 wild type strain 93111 and S. aureus ATCC 25923 as evident by the disc diffusion assay, but Ag-BGsg showed significantly higher mean inhibition zone compared to Ag-BGm. It may be concluded that both Ag-BGsg and Ag-BGm has the potential to be used as bone substitute materials with the Ag-BGsg being more promising due to its high bioactivity and antibacterial effect.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Antibacterial; Bioactive glass; Bioactivity; In vitro; Modified Stöber; Silver

Zinc-containing bioactive glasses for bone regeneration, dental and orthopedic applications - Balasubramanian, Preethi; Strobel, Leonie; Kneser, Ulrich; Boccaccini, Aldo R. (Biomedical Glasses, 2015)